2020
DOI: 10.3389/fphys.2020.00609
|View full text |Cite
|
Sign up to set email alerts
|

Study of sRAGE, HMGB1, AGE, and S100A8/A9 Concentrations in Plasma and in Serum-Extracted Extracellular Vesicles of Pregnant Women With Preterm Premature Rupture of Membranes

Abstract: There was a correlation between plasma and serum-extracted extracellular vesicle concentrations of sRAGE, AGE, HMGB1, and S100A8/A9. Our results suggest that the rupture of fetal membranes (physiological or premature) is accompanied by a variation in plasma concentrations of sRAGE, HMGB1, and AGE. The study of RAGE and its main ligands in extracellular vesicles did not give additional insight into the pathophysiological process conducting to PPROM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…These data further support the idea that HMGB1 may be an important contributor to the initiation of fetal membrane weakening in rupture of membranes (ROM) and pPROM. Additionally, HMGB1 plasma and serum‐extracted extracellular vesicles levels throughout pregnancy have been assessed and HMGB1 plasma concentrations and serum‐extracted extracellular vesicles were found to significantly correlate with both pPROM and normal fetal membranes to promote inflammation 43 . Together, these data suggest that plasma concentrations may contribute to fetal membrane rupture in both normal conditions and pPROM as inflammation is central to membrane weakening in both circumstances.…”
Section: The Role Of Hmgb1 Throughout Gestationmentioning
confidence: 90%
See 3 more Smart Citations
“…These data further support the idea that HMGB1 may be an important contributor to the initiation of fetal membrane weakening in rupture of membranes (ROM) and pPROM. Additionally, HMGB1 plasma and serum‐extracted extracellular vesicles levels throughout pregnancy have been assessed and HMGB1 plasma concentrations and serum‐extracted extracellular vesicles were found to significantly correlate with both pPROM and normal fetal membranes to promote inflammation 43 . Together, these data suggest that plasma concentrations may contribute to fetal membrane rupture in both normal conditions and pPROM as inflammation is central to membrane weakening in both circumstances.…”
Section: The Role Of Hmgb1 Throughout Gestationmentioning
confidence: 90%
“…Therefore, although the assessment of the precise mechanisms of pregnancy complications is often not studied until the fetus is born, there are few situations in which samples can be collected from less invasive approaches such as the assessment of maternal plasma or serum 71 . However, two recent publications were able to elegantly measure the levels of HMGB1 over all of three trimesters and at delivery, the first assessing levels from cultured fetal membranes 42 and the other levels in the maternal circulation throughout pregnancy 43 …”
Section: The Role Of Hmgb1 Throughout Gestationmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, other studies reported an increase in plasmatic esRAGE levels in pPROM but also in placental RAGE levels [ 63 , 98 ]. However, more recently, in 2020, another study found no significant difference in plasmatic sRAGE levels between pPROM and term rupture [ 99 ].…”
Section: The Receptor For Advanced Glycation End Products (Rage)mentioning
confidence: 99%